EPISTEMOLOGICAL DISCOURSE IN A POLITARIAL SOCIETY: CONCEPTUAL OPPOSITION “COGNITIVE” – “RITUAL” - V. Yu. Vasechko (Концепт: философия, религия, культура, 2019)
The article describes the socio-cultural situation in which the individual professionally working on scientific and mathematical problems turns out in politary society (ancient Egypt and Babylon, India and China, medieval Arab-Muslim world, etc.). It focuses on the complex relationship between scientists seeking to uncover the mysteries of nature, and the clergy whose aim is complete control of the process and results of any cognitive activities. Hierocratic estate allows research only to the extent that is necessary for the consolidation of its prerogatives and powers. The conflict of these two cognitive trends largely determines the general character and peculiarities of scientific-cognitive activity in these societies. Existing sacral picture of the world is considered as a firm and perfect one, requiring only minor refinements and specifications. While rituals, committed by clergy, positioned as a necessary condition for the preservation of the natural and social world order. On the contrary, sovereign scientific discourse implies that scientist has a right on free revision of existing views as about the world in general and about specific details of its devices and evolution. The scientist also should not be restricted in finding and applying specific means and methods of cognition of truth. Accordingly, the performance of rituals cannot play a significant role in the picture of the world which is created by scholar’s work. Patterns found in the natural processes are independent from actions committed by various people, including the sacred ceremonies of both ordinary and very senior individuals of spiritual title. Proto-scientific concepts of the universe and particular consequents from them are treated by hierocracyas godless and heretical. In the absence of adequate empirical and theoretical arguments, priests and theologians have to resort in struggle against scholar’s freethinking to force “arguments”. But scientists under favorable conditions can successfully resist this pressure and continue their professional work.